Pengaruh Pelatihan Kerja, Pemberdayaan Karyawan dan Lingkungan Kerja terhadap Kinerja Karyawan - Wati, Yulia Rahma; Baskoro, Ery (Jurnal Manajemen DIVERSIFIKASI, 2021)
This study aims to see the effect of job training, employee empowerment and work environment on employee performance at the Federal International Finance (FIF) Kotabumi.This research was conducted on FIF Kotabumi employees in 2020. By distributing questionnaires in the form of questions about job training, employee empowerment, work environment and employee performance. Then processed with SPSS version 16 with the classical assumption test approach with the methods of normality, linearity, homogeneity.This research uses quantitative methods with multiple linear regression analysis tools, partial test, F test, determination to determine the effect of job training, employee empowerment and work environment on FIF employee performance.The results showed that simultaneously job training, employee empowerment and work environment on employee performance. Research partially shows that job training has no positive and significant effect, while employee empowerment and work environment have a positive and significant effect on employee performance. Keywords: Job Training, Employee Empowerment, Work Environment,EmployeePerformance